The varieties of European colonialism in Central and Eastern Europe: The Polish and the Czech cases - Balogun, Bolaji; Křížová, Markéta (Interventions (London, England), 2025)
This essay examines the Polish and the Czech engagements with colonization. Whilst the present-day Poland and the Czech Republic are often perceived as nations "without colonies", the Central European region throughout the nineteenth and twentieth centuries developed colonial imaginations as part of the "varieties of European colonialism" channeled towards the local needs. By focusing on individuals as well as collective entities linked to various territories in Central and Eastern Europe (CEE), we re-engage the conventional discussions on colonialism from a region often considered peripheral to global colonial histories. The form of colonialism re-engaged here is intrinsic to the processes of inclusion and exclusion that continue to influence the perceptions of "race", Europeanness, and non-Europeanness across CEE.